Evaluación de la influencia de la cobertura vegetal en la protección hidrológica del sitio Brisas – Quiroga, cuenca media del río carrizal - Muñoz Anchundia, Luis Damián (2021)
The main objective of the research was to evaluate the influence of the vegetation cover on the hydrological protection of the Brisas - Quiroga site, middle basin of the Carrizal river, through the Hydrological Protection Index (HPI), for which field visits were made, whose data was used to verify the type of existing vegetation cover in the area, thus obtaining 3 types (wooded area, herbaceous vegetation and cultivated lands), the data was tabulated in the Excel 2016 software and the geographic information system (GIS), due to difficulties in the access to the territory, 3 reference points were taken, in which radiated transects were developed with a total area of 7 ha. The HPI was calculated by using 7 criterias (structure, density, interception, special ecosystems, mulch, type of vegetation and intervention) to which the score of 3, 2 or 1 was awarded, with three being a high indicator and 1 low. The Brisas - Quiroga site has a total area of 157 ha, where the vegetation cover that presented the highest water protection is the wooded area with an HPI of 0.97 followed by cultivated lands with 0.61 and the cover that offers the least protection is herbaceous vegetation with 0.46. Thus, having a total water protection in the place of study of 0,66 ≅ 0,7whose condition is moderately good, of high importance and with an aptitude for conservation, which agrees with the hypothesis raised. The level of accumulated draining cells was also verified by means of the Topographic Moisture Index (ITH), that the basin under study maintains a humidity level of 5.68, being located in 61 hectares (38.83%) of the total surface, thus showing that the area has a medium soil humidity. Finally, a prevention and mitigation plan were developed as a strategy for the management and conservation of the vegetation cover that was aimed at the recovery of the areas affected by deforestation, grazing and by the use of agrochemicals.